Synthesis and Structural Characterization of Copper(II) Complex with Asymmetrical Salen-Type Bisoxime Ligand - Li, Wen-You; Zhang, Yu-Jie; Dong, Xiu-Yan; Li, Xiang; Wang, Li (Asian Journal of Chemistry, 2013)
A new mononuclear Cu(II) complex, [CuL], has been synthesized by the reaction of copper(II) acetate tetrahydrate with H2L (H2L = 4-bromo-6'-methoxy-2,2'-[ethylenediyldioxybis(nitrilomethylidyne)]diphenol). X-Ray crystallographic analysis reveals that the complex crystallizes in the monoclinic system, space group P2(1) and the unit cell contains two crystallographically independent but chemically identical molecules which interlink each other into a 1D infinite chain through four strong intermolecular O12-H12C···O4, O12-H12D···O5, O11-H11C···O9 and O11-H11D···O10 hydrogen bonds.